Rediscovery of Erigeron jaeschkei (Asteraceae: Astereae: Conyzinae) and notes on its correct protologue and typification - Chakraborty, Kasturi; Bhattacharjee, Bandana; Ghosh, Asok; Bhattacharjee, Avishek (Phytotaxa, 2024)
Erigeron jaeschkei (Asteraceae: Astereae: Conyzinae) has been rediscovered after more than 15 decades from the Spiti valley of Himachal Pradesh, India. The protologue of this species name had been cited wrongly in several published literature sources and online databases, which is corrected in the present treatment. Apart from a brief diagnosis and types, no detailed modern description, illustration or photograph was available for this species. Therefore, a detailed description and a colour photo-plate based on our collection are provided for the first time to facilitate identification of this less-known species. A lectotype is also designated from the original collection by Dr. Jäschke.